PERBANDINGAN TINGKAT KEPATUHAN PROTOKOL COVID-19 OPERATOR OJEG ONLINE DAN OJEG KONVENSIONAL DI KOTA MATARAM - I WAYAN SUTEJA; SURYAWAN MURTIADI; ROHANI ROHANI; I GDE PUTU WARKA; HARTANA HARTANA (GANEC SWARA, 2022)
Transportation in general has a major influence on individuals, society, economic development, and socio-politics of a region. Operational aspects must be planned properly so that online motorcycle taxi services and conventional motorcycle taxis can carry out their functions as Modern City Transportation economically, efficiently and effectively. In this post-pandemic period, we know that there are differences in the characteristics of online motorcycle taxis and conventional motorcycle taxis in providing services to their users.By conducting survey research based on the level of explanation is descriptive research, to obtain characteristic data the researcher has distributed questionnaires to 400 respondents who are online motorcycle taxi users and 400 respondents who are conventional motorcycle taxi users. The two characteristics turned out to be quite similar to each other. The total population of motorcycle taxi users is 486,715 (Mataram City in figures, 2019). By using the formula for calculating the number of samples from Slovin (Statistical Formula, 2012) and a 95% confidence level, the total sample size is 400 respondents.The results of the synthesis of these two characteristics can be conveyed as follows: Gender of users is dominated by women as much as 58.8%, the purpose of the trip is dominated by work and shopping trips 51.87%, the mode before switching is dominated by motorcycle modes as much as 59.5%, connecting trips The distance to the base is dominated by a distance of 0-1 km, the connecting trip from the stop to the destination is dominated by a distance of 0-1 km using walking mode